Plasma brain injury markers are associated with volume status but not muscle health in heart failure patients - Lahiri, Shouri; Mastali, Mitra; Van Eyk, Jennifer E.; Hitzeman, Tara C.; Bresee, Catherine; Raedschelders, Koen; Lyden, Patrick D.; Gottlieb, Roberta A.; Fang, James C.; Shaw, Robin M.; Hong, Ting Ting (Frontiers in Drug Discovery, 2022)
Background: Neurofilament light chain protein (NfL) and tau are plasma biomarkers of neuronal injury which can be elevated in patients with neurodegenerative diseases. N-terminal pro-brain natriuretic peptide (NT-proBNP) is an established marker of volume status in patients with heart failure (HF) and plasma cBIN1 score (CS) is an emerging biomarker of cardiac muscle health. It is not known if, in HF patients, there is a correlation between cardiac markers and brain injury markers. Methods: We studied ambulatory HF patients with either preserved and reduced ejection fraction (N=50 with 25 HFrEF and 25 HFpEF) and age and sex matched healthy controls (N=50). Plasma NT-proBNP and CS were determined using commercial kits. A bead-based ELISA assay was used to quantify femtomolar concentrations of plasma neuronal markers NfL and total tau. Results: Plasma levels of NT-proBNP and CS in heart failure patients were significantly higher than those from healthy controls. In both patients with HFrEF and HFpEF, we found independent and direct correlations between the volume status marker NT-proBNP, but not the cardiomyocyte origin muscle health marker CS, with NfL (r=0.461, p=0.0007) and tau (r=0.333, p=0.0183). Conclusions: In patients with HF with or without preserved ejection fraction, plasma levels of NfL and tau correlate with volume status rather than muscle health, indicating volume overload-associated neuronal injury.